ANALISIS TINGKAT KESEHATAN BANK UMUM SYARIAH SEBELUM DAN SESUDAH SPIN-OFF - Sonia Putri Govina; Rafika Rahmawati; Rizal Pahlevi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
The spin-off is carried out to gain a large influence in improving the company's condition and improving financial health. With the change in the Sharia Business Unit that carries out a spin-off, the soundness of the Sharia Business Unit will increase and encourage other Sharia business units to do a spin-off. This study aims to compare the financial health level of Islamic Commercial Banks before and after the Spin-Off using the RBBR method at PT. BTPN Syariah. The method used in this research is the comparison method of non-parametric statistical tests of two related samples, namely using the Wilcoxon Signed Ranks Test Differential Test. The research data used are financial reports from the fourth quarter of 2008 - the third quarter of 2021. The results of this study on the Wilcoxon Signed Ranks Test showed a significant difference in the health level of PT. BTPN Syariah before and after Spin-Off on FDR, ROA, NIM/NOM, and CAR indicators. While the indicators for NPF, BOPO, and GCG, there are no significant differences before and after the Spin-Off. Differences in FDR, ROA, NIM/NOM, and CAR indicators can incentivize other Sharia Business Units to carry out Spin-Offs.